North West Cross Institutional Action Learning developing women's leadership. (2nd September 2018) - Box, Meriel; Ellis, Tracy
ABSTRACT: Human resource development professionals in Higher Education are continually striving to develop efficient interventions to increase the capabilities of their leaders. As a result of evaluating feedback from an action learning (AL) programme designed and delivered in North West Higher Education Institutions in the UK for women in senior academic and professional service roles, we are able to share how AL can be utilised to transcend and supplement traditional leadership training. The article discusses the approach taken to support participants to develop vital leadership behaviours through the acquisition of critical questioning and reflective habits whilst developing strong supportive cross-institutional relationships with other higher education leaders.